Implementation of Community Policing Strategy: Impact of Community Factors in Nairobi Country - Gichangi Kabage, Robert (International Journal of Scientific Research and Management (IJSRM), 2019)
Crime is a community problem and not just a police problem. The adoption and implementation of Community Policing (CP) in the 1980s, was perceived as departure from the professional ‘police-as-expert’ model of public safety that had been dominant for a long time. The CP approach is designed to engage the community as an equal partner in solving local crime and other security threats within the community. The CP concept was introduced in Kenya in the 1990s.Though it had informally existed in Nairobi County in Ruai and Kasarani estates much earlier.Its formal implementation only gained currency after the Post Election Violence of 2007-2008 in Kenya. Among the factors influencing its implementation in Kenya has received considerable research attention, but challenges impacting on its implementation in Nairobi County have not been adequately documented. This study aimed to fill this research gap by focussing on community factors. The overall research objective sought to determine the influence of community factors in effective implementation of community policing within Nairobi County. The objective of the study was to assess how community factors influence implementation of community policing within Nairobi County. The research findings adds to the body of knowledge, while also benefitting policy makers dealing with issues of community policing. It will also benefit other researchers exploring different aspects of community policing as a strategy to combat crime in city neighbourhoods. The research established that community factors are among the most influential factors that hamper smooth implementation of community policing in Nairobi County. The study recommends that the community needs to be educated on community policing initiatives and how to manage community factors that affect the implementation of CP in Nairobi County.